Implementasi Kebijakan Rencana Tata Ruang Wilayah (RTRW) dalam Pemanfaatan Ruang Terbuka Hijau (RTH) Publik Pusat Kota di Kabupaten Lamongan - Aufa Anggarda , Achmad; Purnaweni , Hartuti; Suwitri , Sri (Jurnal Ilmiah Administrasi Publik, 2024)
The downtown area is used as a benchmark in assessing the development of a city, including the downtown area of Lamongan Regency. However, the downtown area of Lamongan Regency has not been able to optimize the potential of public green spaces as a support for the city center according to the policy. The research aims to examine the implementation of spatial planning policies in the utilization of public green spaces in the downtown area of Lamongan Regency. This research uses a descriptive-qualitative method. The results show that the implementation of the policy on the utilization of public green spaces in the development of new public green spaces has a total development percentage of 7.7%, which does not align with the policy. Maintenance of public green spaces is carried out according to the maintenance standard operating procedure (SOP). It is recommended that the Environmental Agency of Lamongan Regency provide training based on the competence of employees, manage available funds efficiently, request additional needed budget, and conduct public awareness campaigns on public green spaces through information in mass media and social media